2020
DOI: 10.47360/1995-4484-2020-376-386
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of netakimab, anti-IL-17A monoclonal antibody, in patients with ankylosing spondylitis. Results of phase III international, multicenter, randomized double-blind clinical trial BCD-085-5/ASTERA

Abstract: Netakimab (NTK) is a humanized monoclonal antibody targeting interleukin-17A.Objective. The main objective of BCD-085-5/ASTERA study was to prove superiority of NTK over placebo and assess its’ safety in patients with active AS.Subjects and methods. BCD-085-5/ASTERA was a double-blind, multicenter, randomized, placebo-controlled, phase III study, which included 228 adult patients with active AS, persisting despite active treatment with NSAIDs. AS was considered active at BASDAI score ≥ 4.0. Patients were blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A phase II dose-ranging study of bimekizumab, which neutralises both IL-17A and IL-17F, found response rates higher than with placebo in r-axSpA (ASAS40 29.5–45.9% vs 13.3%, low RoB) 38. Finally, netakimab was found to be efficacious in two phase II/III trials with unclear RoB, in patients with r-axSpA (ASAS40 40.4–72.7% vs 2.6–14.3%) 36 37…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A phase II dose-ranging study of bimekizumab, which neutralises both IL-17A and IL-17F, found response rates higher than with placebo in r-axSpA (ASAS40 29.5–45.9% vs 13.3%, low RoB) 38. Finally, netakimab was found to be efficacious in two phase II/III trials with unclear RoB, in patients with r-axSpA (ASAS40 40.4–72.7% vs 2.6–14.3%) 36 37…”
Section: Resultsmentioning
confidence: 97%
“…In total, 14 placebo-controlled trials assessed the efficacy of IL-17i (table 2, online supplemental tables S3.37−S3.66). 26–39 Patients with r-axSpA on secukinumab showed greater improvement compared to placebo in two phase III trials (ASAS20 58.1–60.5% vs 36.6–36.8%, low/unclear RoB) 26 28. Another phase III trial at low RoB saw numerically higher response rates for secukinumab compared to placebo in patients with r-axSpA, although results were not statistically significant (ASAS20 59.5–61.5% vs 47.0%) (table 3).…”
Section: Resultsmentioning
confidence: 98%
“…In ASTERA, ASAS40, response rates were 40.4% with NTK vs 2.6% with placebo at week 16. 14 In PATERA, a higher proportion of patients reached American College of Rheumatology (ACR) 20 (82%) and ACR50 (70%) at week 24 with NTK vs placebo (9% and 6%, respectively). 15 Approved since 2016 in Japan for treating PsA, brodalumab is a fully human monoclonal antibody that binds to the IL-17 receptor subunit A (IL-17RA) and inhibits the activity of both IL-17A and F. For axSpA, a completed phase III trial showed positive results with ASAS40 response rates of 45.5% at week 16 and 61.6% at week 68.…”
Section: Resultsmentioning
confidence: 97%